Relational Literacy - W. Kurt Stavenhagen (Journal of the Assembly for Expanded Perspectives on Learning, 2019)
In this paper, I propose literacy practices that further shift us from subject-object dichotomies and exclusive language practices to a focus on relationships and multimodality. Based in large part upon Indigenous Scholar Shawn Wilson’s concept of relationality, I define a relational literacy wherein we counter an undue abstraction of the environment by mapping interspecies relationships and placing them within kinship narratives.